Banthưk khwāmkhl̄ưanwai karanī khrōngkān th̨̄o song kāt Thai-Phamā (Klum Khanāčhān Mahāwitthayālai Chīang Mai ph̄ưa Prachāthipatai læ Singw̄ætl̨̄om, 1998)
Review on effects of natural gas pipeline project from Thailand to Burma on environment and human rights in Thailand.